全球化脈絡下大學擴充對高等教育資源分配之影響 Resource Distribution of Higher Education in the Age of Globalization - 劉欣宜Hsin-Yi Liu (Higher Education Foundation, 2005)
高等教育在全球化的影響下，逐漸朝大眾化、市場化、多樣化等趨勢發展，同時在資金分配方式及大學自主本質上亦有所轉變。惟近年來我國大學教育擴充過速，導致產生資源稀釋的情況，高等教育也因此面臨辦學品質低落、大學性質丕變、經費排擠效應、資源爭奪風暴、學校貧富不均及社會正義枉顧等危機，本文即以此為探討重點，進行深度分析，繼而提出整合校際與校內資源、建立合理的經費分配方式、釐清學校功能與定位做重點發展、擴大公立大學自籌財源的方向等可行的因應策略以供參考。 Under the globalization trend, the higher education faces the changing of structure and management, such as massification, makertization and multiversity of higher education. Because of these impacts, the higher education may meet problems of lowering schooling quality, lacking of resources, and neglecting social justice. The aim of this study is to focus on this point, and to provide some practical suggestions for reference.